PERHITUNGAN FLUKS KALOR UNTUK KURVA DIDIH SELAMA EKSPERIMEN QUENCHINGMENGGUNAKAN SILINDER BERONGGA DIPANASKAN - Juarsa, Mulya; Koestor, Raldi Artono; Putra, Nandy Setiadi Djaya; Antariksawan, Anhar Riza; Mulyana, Cukup; Khalisa, Riska (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
One of the safety management aspects in the operation of nuclear reactors is thermal management. The basic concept of thermal management is to control the excess heat during an accident. The understanding and investigation of boiling phenomenon become important research stage. Quenching process is the process of sudden cooling on a hot object by entering into a fluid. SS316 material with hollow cylinder geometry in a vertical position is the simulation of debris and used as a heated object. Method of quenching experiments carried out through the natural cooling of the hollow cylinder with different variations of initial temperature from 300 oC to 800 oC and submerged into the water with saturation temperature. Temperature data was recorded and boiling was captured using highspeed camera (HSC) during the experiment. The results of transient temperature data was used to calculate the heat flux. The film boiling regime on TC8 (outer portion) in the boiling curves for all initial temperatures have a good agreement with Bromley’s correlation. The shortest process of film boiling was occurred for 1.11 seconds at the initial temperature of 300oC. Critical heat flux at TC8 from initial temperature of 800 oC, 600 oC, 400 oC and 300 oC in respectively is 700 kW/m2, 500 kW/m2, 450 kW/m2 and 400 kW/m2.